Nursing interventions during the covid-19 pandemic: The decisive role of patients’ dependency levels - Bilgin, Nurcan; Derviş, Ezgi Bolat (Acta Scientiarum. Health Sciences, 2025)
To determine the dependency levels of patients and the nursing interventions in a pandemic clinic, and to examine the decisive role of patient dependency levels in nursing interventions. This research is a retrospective descriptive study. The sample of the research was composed of 108 Covid-19 patients hospitalized in Turkey. The data was obtained from electronic patient records of the hospital. Data analysis was carried out using descriptive statistics, and Chi-square test for trend analysis. In this research, 49.1% of the Covid-19 patients hospitalized were in moderately and highly dependent patient groups. Indirect nursing interventions were performed to all patients, and direct nursing interventions determined based on patients’ needs were not performed to all patients. It was found that there was a linear relationship between all nursing interventions and dependency levels (p < 0.001). It was concluded that the dependency levels of patients and the nursing interventions performed by nurses were affected in the Covid-19 pandemic. Nurse managers should take into account that patients’ dependency levels affect the implementation of nursing interventions and ensure that patient care is provided by considering their dependency levels during the pandemic process.